Simultaneous determination of three alkaloids, four ginsenosides and limonin in the plasma of normal and headache rats after oral administration of Wu‐Zhu‐Yu decoction by a novel ultra fast liquid chromatography‐tandem mass spectrometry method: application to a comparative pharmacokinetics and ethological study. (10th April 2013) - Xu, Huarong; Li, Qing; Yin, Yidi; Lv, Chunxiao; Sun, Wanyang; He, Bosai; Liu, Ran; Chen, Xiaohui; Bi, Kaishun
<x xml:space="preserve">Abstract</x> A novel, sensitive and reliable ultra fast liquid chromatography‐tandem mass spectrometry (UFLC‐MS/MS) method has been developed and validated for simultaneous quantitation of eight main active ingredients (evodiamine, rutaecarpine, dehydroevodiamine, limonin, ginsenoside Rb1, Rd, Re and Rg1) in rat plasma after oral administration of Wu‐Zhu‐Yu (WZY) decoction, which is a celebrated and widely used Traditional Chinese Medicine formula for the treatment of headache. The analytes and internal standard (IS) were separated on a SHIM‐PACK XR‐ODS II column, and the detection was performed on a UFLC‐MS/MS system with turbo ion spray source. The lower limits of quantification were 1.5, 0.5, 1.0, 2.0, 2.0, 1.0, 0.5 and 0.2 ng ml−1 for evodiamine, rutaecarpine, dehydroevodiamine, limonin, gensenoside Rb1, Rd, Re and Rg1, respectively. Linearity, accuracy, precision and absolute recoveries of the eight analytes were all within satisfaction. The IS‐normalized matrix factor was adopted for assessing the matrix effect and accompanied with a satisfactory result. The validated method has been successfully applied to compare pharmacokinetic profiles of the eight active ingredients in rat plasma between normal and headache rats after administration. Exact pharmaceutical effect of WZY decoction on headache was demonstrated by the ethological response of headache rats induced by nitric oxide donor after administration. The results indicated that the absorption of evodiamine, rutaecarpine, gensenoside Rb1, Re and Rg1 in headache group were significantly higher than those in normal group with similar concentration–time curves while no significant differences existed in limonin and ginsenoside Rd between the two groups. Copyright © 2013 John Wiley & Sons, Ltd.